2015
DOI: 10.3892/mco.2015.705
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative mean corpuscular hemoglobin affecting long-term outcomes of hepatectomized patients with hepatocellular carcinoma

Abstract: Abstract. Pretreatment anemia has been reported to be associated with survival in several solid tumor types. In terms of survival, only limited data on the hemoglobin (HGB) level in hepatocellular carcinoma (HCC) have been published and no data on mean corpuscular hemoglobin (MCH) level in HCC is available. The present study sought to examine the role of HGB and MCH levels in predicting long-term survival of patients with HCC who undergo resection. A retrospective study of 399 consecutive patients (1987)(1988)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Among the included studies, 18 studies[ 15 , 17 , 22 , 24 , 25 , 27 - 32 , 34 - 40 ] reported 30-d mortality rates whereas only two studies[ 36 , 39 ] reported 90-d mortality rates (Figure 4 ). While resection of non-giant HCC had lower odds of death within the first 30 d after surgery, the difference was not statistically significant (OR 0.73, 95%CI: 0.50-1.08, P = 0.116).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies, 18 studies[ 15 , 17 , 22 , 24 , 25 , 27 - 32 , 34 - 40 ] reported 30-d mortality rates whereas only two studies[ 36 , 39 ] reported 90-d mortality rates (Figure 4 ). While resection of non-giant HCC had lower odds of death within the first 30 d after surgery, the difference was not statistically significant (OR 0.73, 95%CI: 0.50-1.08, P = 0.116).…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, 20 studies[ 14 - 16 , 21 - 25 , 27 - 34 , 36 - 38 , 40 ] reported on vascular invasion, 13 studies[ 15 , 16 , 21 , 22 , 24 , 27 - 29 , 31 , 32 , 37 , 39 , 40 ] on cirrhosis, 16 studies[ 15 , 16 , 22 , 23 , 25 , 27 , 28 , 30 - 37 , 39 , 40 ] on Child Pugh’s score and 9 studies[ 21 , 22 , 24 , 27 , 29 , 32 , 34 , 37 , 40 ] on tumor number (Table 3 ). While non-giant HCC was found to have significantly lower odds of vascular invasion (OR 0.367, 95%CI: 0.236-0.572, P < 0.0001) and multinodular tumors (OR 0.592, 95%CI: 0.376-0.939, P < 0.0259), it was found to have significantly higher odds of cirrhosis (OR 1.955, 95%CI: 1.317-2.903, P = 0.0009).…”
Section: Resultsmentioning
confidence: 99%
“… 26 Anemia is a common complication in HCC patients, and previous evidence has indicated its correlated with poor clinical prognosis in HCC. 27 Elevated hemoglobin levels may be a compensatory response to the presence of massive tumors that have outgrown their vascular supply, leading to local ischemia and hypoxia. 28 The association between high hemoglobin levels and poor survival observed in our study suggests that this phenomenon may serve as a prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…MCH is a measurement of the average HGB content of each RBC ( 11 ). One small-scale retrospective study revealed that a low MCH level was associated with worse survival in hepatectomized patients with hepatocellular carcinoma ( 11 ), and MCH was shown to be a marker of iron metabolism. As demonstrated in previous reports, abnormalities in iron metabolism might be crucial in cancer progression ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…MCV is a measurement of RBC size ( 9 ), which could reflect folate deficiency ( 10 ). MCH refers to a calculation of the average HGB content of each RBC, another factor correlated with anemia that represents the iron metabolism ( 11 ). MCHC is calculated by dividing the HGB by the HCT and can reflect average HGB concentration ( 12 ).…”
Section: Introductionmentioning
confidence: 99%